Gonadal Hormones Contribute to Sex Differences in Autoimmunity, Pathology and Behaviour in the 3×Tg‐AD Mouse Model of Alzheimer's Disease. (20th December 2022) - Fahnestock, Margaret; Song, Wei; Ma, Donglai; Creighton, Samantha D; Mian, Firoz; Michalski, Bernadeta; Forsythe, Paul; Sakic, Boris; Zovkic, Iva
Abstract: Background: Sex‐dependent discrepancies in prevalence and autoimmune markers are characteristics of Alzheimer's disease (AD). Using the 3xTg‐AD mouse model, we previously reported that adult males show early systemic autoimmunity along with behavioural dysfunction, altered epigenetic factors, and lack of plaque/tangle pathology. Conversely, adult females display less severe autoimmunity and retain AD‐like pathology and behaviour. The present study examines whether gonadal hormones play a role in the etiology of these traits in current cohorts of 3xTg‐AD mice. Method: 3xTg‐AD and wild‐type mice were gonadectomized or sham‐operated at 3 months of age. After behavioural phenotyping at 6 months of age, the animals were assessed for serologic markers of autoimmunity, T splenocyte distribution, molecular markers of AD pathology, and expression of genes and histone variants associated with neurodegeneration. Result: In female transgenic (AD) mice, gonadectomy resulted in reduced levels of circulating antinuclear/nucleosome autoantibodies and poorer spatial learning performance, but did not affect the T cell population. In contrast, in transgenic male animals, gonadectomy improved spatial memory and cognitive flexibility, diminished splenic CD8+ T cells, yet had no impact on anti‐nuclear/nucleosome autoantibodies. Sex hormone‐related effects on anti‐nucleosome autoantibodies led us to focus on histones. Gonadectomized AD females exhibited enhanced expression of mouse (m) and transgenic Mapt genes, consistent with reduced binding activity of the repressive histone variant macroH2A1 at the m Mapt gene body, compared to their sham counterparts. In contrast, gonadectomized AD males showed reduced expression of App and H2afy genes, reduced cortical soluble Aβ42 levels, and increased macroH2A1 binding at the m Psen1 promoter, compared to sham‐operated AD males. Conclusion: Female sex hormones enhance autoimmunity and spatial learning, whereas male sex hormones may be detrimental to spatial memory, cognitive flexibility, and autoimmunity in young adulthood. Furthermore, female sex hormones increase expression of the Mapt gene, but have no effect on App expression or Aβ42 levels. Conversely, male sex hormones increase App expression and Aβ42 levels, but have no effect on tau expression. Our work suggests that gonadal hormones contribute to sex differences in autoimmunity, AD‐like pathology, and "cognitive" function in this model. Moreover, histone variants may contribute to sex‐specific differences in AD pathology.